ISOTOPIC AGE OF RHYOLITES FROM THE TRIASSIC TURA GROUP OF THE KUSHMURUN GRABEN, THE TURGAI DEPRESSION - Rublev A.G.; Proshin E.E.; Shergina Yu.P.; Bogomolov E.S. (My University, 2001)
Isotopic dating showed that rhyolites of the Kushmurun graben are divisible into two groups different in age. One group is close to the Induan-Olenekian boundary in its chronostratigraphic position and has K-Ar and Rb-Sr age of 247 ± 3 Ma. The Rb-Sr isochron age for another group is 162 ± 7 Ma and thus corresponds to the Middle Jurassic. The results obtained suggest that the available stratigraphic subdivision of deposits in the Kushmurun graben should be revised. They also elucidate the isotopic age of the Induan-Olenekian boundary.
Keywords: Kushmurun graben; Isotopic dating; Triassic; Jurassic; Mesozoic::Jurassic; Мезозой::Юрская; Мезозой::Триасовая; Mesozoic::Triassic